Effects of Ramadan fasting on physical performance and metabolic, hormonal, and inflammatory parameters in middle-distance runners - Chennaoui, M.; Desgorces, F.; Drogou, C.; Boudjemaa, B.; Tomaszewski, A.; Depiesse, F.; Burnat, P.; Chalabi, H.; Gomez-Merino, D. (Applied Physiology, Nutrition, and Metabolism, 2009)
The Ramadan fasting (RF) period is associated with changes in sleep habits and increased sleepiness, which may affect physical performance in athletes, and may induce metabolic, hormonal, and inflammatory disturbances. In 8 middle-distance athletes (25.0 ± 1.3 years), a maximal aerobic velocity (MAV) test was performed 5 days before RF (day -5), and on days 7 and 21 of RF. The same days, saliva samples were collected to determine cortisol and testosterone concentrations before and after the MAV test. Blood samples were collected before RF (P1), at the end of RF (P2), and 1 week post RF (P3). Plasma levels of interleukin (IL)-6, a mediator of sleepiness and energy availability, were determined. We also evaluated changes in metabolic and hormonal parameters, mood state, and nutritional and sleep profiles. During RF, mean body mass and body fat did not statistically change. Compared with day -5, MAV values decreased at days 7 and 21 (p < 0.05, respectively), while testosterone/cortisol ratio values did not change significantly. Nocturnal sleep time and energy intake were lower at day 21 than before RF (day 0/P1) (p < 0.05). At the end of RF (day 31), the fatigue score on the Profile of Mood States questionnaire was increased (p < 0.001). For P2 vs. P1, IL-6 was increased (1.19 ± 0.25 vs. 0.51 ± 0.13 pg/mL; p < 0.05), melatonin levels were decreased (p < 0.05), and adrenalin and noradrenalin were increased (p < 0.01 and p < 0.001, respectively). At 7 days post RF, all parameters recovered to pre-RF values. In conclusion, RF is accompanied by significant metabolic, hormonal, and inflammatory changes. Sleep disturbances, energy deficiency, and fatigue during RF may decrease physical performance in Muslim athletes who maintain training. Reduction of work load and (or) daytime napping may represent adequate strategies to counteract RF effects for Muslim athletes.